2009
DOI: 10.1093/eurpub/ckp122
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette pack design and perceptions of risk among UK adults and youth

Abstract: Current regulations have failed to remove potentially misleading information from tobacco packaging. Removing colours from packs (plain packaging), as well as terms such as 'smooth' 'gold' and 'silver' would significantly reduce false beliefs and increase compliance with existing legislation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
163
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(181 citation statements)
references
References 18 publications
13
163
4
1
Order By: Relevance
“…11 E-cigarette marketing is a source of product information for many consumers 12 and is increasing rapidly. 4,[13][14][15][16] Previous research has found that exposure to tobacco marketing can result in public misinformation about the risks of tobacco use 17,18 and incorrect beliefs. 19,20 Consumers may believe that e-cigarettes are safer than cigarettes partly due to the marketing messaging, which make e-cigarettes look more appealing and less harmful than combustible tobacco cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…11 E-cigarette marketing is a source of product information for many consumers 12 and is increasing rapidly. 4,[13][14][15][16] Previous research has found that exposure to tobacco marketing can result in public misinformation about the risks of tobacco use 17,18 and incorrect beliefs. 19,20 Consumers may believe that e-cigarettes are safer than cigarettes partly due to the marketing messaging, which make e-cigarettes look more appealing and less harmful than combustible tobacco cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, our findings showed that although "lights" smokers who believed that "lights" are less harmful were more likely to believe that "lights" are smoother (80.4%), most "nonlights" smokers (81.2%) also held similar beliefs. We did not ask about ever use of "lights", and so we do not know whether perceptions of smoothness by "non-lights" users were based on past actual sensory experience with "lights", or whether this is consistent with previous research 30,31 that showed that perceptions of harm are also influenced by product packaging and marketing (e.g., lighter colors on cigarette packages are perceived as less harmful). The lack of a difference in both beliefs (i.e., smoothness and harmfulness) between "lights" and "non-lights" smokers in our study, demonstrates the strength of the perceived linkage between smoothness and harmfulness.…”
Section: Discussionmentioning
confidence: 80%
“…The public health debate addresses three main themes: (i) reduction of the symbolic value of tobacco packaging (Wakefield et al, 2012;Borland et al, 2013;Ford et al, 2013a;Moodie and MacKintosh, 2013;Scheffels and Saebø, 2013); (ii) reinforcement of consumers' health attitude towards smoking, increased recall and perceived seriousness of health messages (Hammond et al, 2009;Munafò et al, 2011;AlHamdani, 2013;Maynard et al, 2013;Moodie and MacKintosh, 2013); (iii) evidence of behavioural change (e.g., attempts to quit, quit-line calls, reduced consumption; Moodie et al, 2012Chantler, 2014;Maynard, 2014). For a systematic review of plain packaging conducted from a public health perspective, see Moodie et al (2012.…”
Section: Introductionmentioning
confidence: 99%